Influence Of Entrepreneurial Motivation, Entrepreneurship Education, And Family Environment On Interest In Entrepreneurship Among Students - Ridwan, Farid; Putri, Ratna Komala (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to investigate the influence of entrepreneurial motivation, family environment and entrepreneurship education on the entrepreneurial interest of the students at Widyatama University, Bandung. In this study, 100 students as the study samples were taken out of the population which accounted for 127 students of the University of Widyatama Bandung majoring in Management in 2016 who took the minor in entrepreneurship. The samples were taken using primary data in the form of questionnaires and a modified Likert scale for data collection technique. Subsequently, the data were then analyzed using multiple linear analysis with the aid of SPSS 23 for processing statistical data. In this study, there were several variables under investigation, such as X1 (entrepreneurial motivation), X2 (family environment), X3 (entrepreneurship education), and Y (entrepreneurial interest).Based on the results of multiple linear analysis, it reveals that entrepreneurial motivation and education as well as family environment simultaneously have a significant influence on the interest in entrepreneurship of the students at Widyatama University, Bandung. Furthermore, the entrepreneurial motivation is the most dominant variable which influences the interest in enetrepreneurship among the others. Finally, the coefficient of determination is 0.360 or 36%, while the rest is influenced by other factors which were not examined in this study.